The response of mulberry trees after seedling hardening to summer drought in the hydro-fluctuation belt of Three Gorges Reservoir Areas - Huang, Xiaohui; Liu, Yun; Li, Jiaxing; Xiong, Xingzheng; Chen, Yang; Yin, Xiaohua; Feng, Dalan (Environmental science and pollution research international, 2013)
Interest has developed in the potential of mulberry ( Morus alba ), a woody perennial, for revegetating the hydro-fluctuation belt of the Three Gorges Reservoir due to its resistance to water-logging stress. To be useful, the trees must also be able to withstand dry conditions in summer when temperatures can be very high and droughts become severe quickly. Here, we report a study in which mulberry seedlings were grown in a greenhouse under a variety of simulated soil water conditions reflecting potential summer scenarios in the hydro-fluctuation belt of the Three Gorges Reservoir Area. We compared the responses of two pretreatment groups of mulberry seedlings to different levels of drought stress. The pretreatment groups differed with respect to drought hardening: the daily-managed (DM) group had relative soil moisture held constant in the range 70–80 %, while the drought-hardened (DH) group had relative soil moisture held constant at 40–50 %. Following the month-long pretreatment of seedlings, the two groups of young trees (DM and DH) were then respectively subjected to three levels of drought stress for a month: normal watering, moderate drought stress, and severe drought stress. A series of measurements comparing the physiological status of the plants in the two groups were then made, and the following results were obtained: (1) As drought stress increased, the heights, base diameters, root surface areas, photosynthetic rates (Pn), stomatal conductances (Gs), and transpiration rates (Tr) of the mulberry trees in both groups (DM and DH) decreased significantly, while the specific root area and abscisic acid (ABA) contents had increasing trends. Root activity and instantaneous water use efficiency of mulberry trees in both groups (DM and DH) were all raised under drought stress conditions than under normal watering, but the root/shoot ratio and leaf water potential were lowered. (2) At the same level of soil water content, the heights, base diameters, root/shoot ratios, root surface areas, specific root areas, photosynthetic rates (Pn), stomatal conductances (Gs), and transpiration rates (Tr) of the young mulberry trees in the DH were all significantly higher than those of the control group (DM). Leaf water potential, instantaneous water use efficiency, and abscisic acid content of DH were all significantly lower than DM. Under different degrees of drought stress, the growth of mulberry trees will be inhibited, but the trees can respond to the stress by increasing the root absorptive area and enhancing capacity for water retention. Mulberry trees demonstrate strong resistance to drought stress, and furthermore drought resistance can be improved by drought hardening during the seedling stage.